SAIS service quality and student's satisfaction towards the implementation of Student Activity Information System (SAIS): The moderating role of SAIS service convenience - Norshima Humaidi; Melissa Shahrom; Muhamad Sukor Jaafar; Siti Halijjah Shariff (Foundations of Management, 2019)
Student Activity Information System (SAIS) was developed with the aims to efficiently record the applications of student's activity at the Faculty of Business and Management (FBM), Universiti Teknologi MARA (UiTM) Selangor, Malaysia and to assist the administrator to manage the students' activities effectively. By using different e-service quality dimensions, this study proposed a higher order factor of SAIS Service Quality with an attempt to determine a moderating effect of SAIS Service Convenience between the relationship of SAIS Service Quality and Student's Satisfaction. Quantitative data was gathered from 94 SAIS users and the data were analyzed by using SmartPLS 3.0. The analysis result showed that SAIS Service Quality and SAIS Service Convenience were positively influenced the student's satisfaction. Moreover, the result also revealed that the higher order factor of SAIS Service Convenience was not to moderate the relationship between the SAIS Service Quality and Student's Satisfaction. From the Higher Education (HE) perspective, this study provides an empirical validation of the Information System Service Quality Model particularly in the context of SAIS. Hence, the improvement of the e-service quality is essential for future enhancement of existing information systems in the higher education institutions.
Keywords: H80; I23; J24; L23; O31; 650; information system; student's activity; higher education; e-service quality; service convenience